Supporting the Design, Commissioning and Supervision of Smart Factory Components through their Digital Twin - Martins, André (2020)
In a context of greater complexity of Smart Factories, the commissioning time for automated systems needs to be shortened. The use of virtual commissioning tools is a good contribution to achieve this goal. Ideally, those tools should be part of a virtual engineering environment sharing same virtual model, the digital twin, through the complete lifecycle of the automated system, namely the project, simulation, implementation and execution/monitoring/supervision and, eventually decommissioning phases. Such vision includes a digital twin with a broader use, which is consistent with the real system and one that can be used after the early design and commissioning phases. Finding a complete set of tools able to comply with the above requirements can be extremely challenging. In this paper we explore the use of the ABB RobotStudio software combined with the OPC UA standard with this vision in mind. Methodologies were defined to integrate both new generation and legacy equipment, as well as robot controllers and guidelines for equipment development. A key result of this work is the development of a set of virtual engineering tools and methodologies based on OPC UA and implemented using RobotStudio in order to accomplish the complete lifecycle support of an automated system, from the project and simulation phases, to the monitoring and supervision phases, suitable for integration in Industry 4.0 factories. Results are described for a test scenario with different devices.